2016
DOI: 10.1016/j.ijrobp.2016.06.2455
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Pelvic Irradiation in Localized Prostate Adenocarcinoma? Update of the Long-Term Survival Results of the GETUG-01 Randomized Study

Abstract: Pelvic nodes irradiation did not statistically improve EFS or OS in the whole population but may be beneficial in selected low- and intermediate-risk prostate cancer patients treated with exclusive radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
117
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 27 publications
1
117
0
1
Order By: Relevance
“…GETUG-01 was a French randomized trial that did not show a benefit in overall survival or progression-free survival with WPRT, though the radiation dose (mean total dose of 68 Gy) was low by modern standards [27]. In contrast, Aizer et al retrospectively demonstrated significant improvement in biochemical control with pelvic RT with use of higher dose (mean 75.6 Gy); however, longer follow-up is needed [28].…”
Section: Discussionmentioning
confidence: 99%
“…GETUG-01 was a French randomized trial that did not show a benefit in overall survival or progression-free survival with WPRT, though the radiation dose (mean total dose of 68 Gy) was low by modern standards [27]. In contrast, Aizer et al retrospectively demonstrated significant improvement in biochemical control with pelvic RT with use of higher dose (mean 75.6 Gy); however, longer follow-up is needed [28].…”
Section: Discussionmentioning
confidence: 99%
“…The pelvis was treated with a four field technique to 46Gy and the prostate treated to initially 66Gy but was subsequently increased to 70Gy as the trial progressed. After a median follow-up of 11.4 years, there was no statistically significant difference in overall survival (74.9% vs 73.6% p = 0.18) or event free survival (57.6% vs 55.6% p = 0.9715) between pelvic or prostate RT [25]. Somewhat surprisingly in a post hoc subgroup analysis there was a 15% improvement in event free survival for those with a low risk of lymph node involvement (<15%-Roach formula), but this was not deemed clinically significant when interpreting data with a limited effective size (approximately 20% of the cohort), and moreover any advantages were observed predominantly in patients who did not receive any ADT [25].…”
Section: The Benefit Of Elective Nodal Irradiationmentioning
confidence: 84%
“…Yet when comparing the WPRT + NHT arm to the PORT + NHT arm there was a trend towards statistical significance in the endpoints of PFS (p = 0.023) [24]. It is important to note that approximately 50% of patients in the GETUG-01 trial had a low risk of pelvic nodal involvement, with only approximately 11% having Gleason 8 or greater tumours, and just 25% with T3 disease [25]. As such this selection weakens the conclusion about the lack of benefit from WPRT.…”
Section: The Benefit Of Elective Nodal Irradiationmentioning
confidence: 98%
“…In multiple surgical series , a significant portion of patients with high‐risk PCa harboured nodal disease, as confirmed by ePLND, suggesting that it is reasonable to perform pelvic RT in men with high‐risk PCa who plan to undergo RT. However, some physicians doubt the use of pelvic RT, as two randomized controlled trials demonstrated no significant benefits of the approach among patients with intermediate‐ or high‐risk PCa . In the randomized phase III Radiation Therapy Oncology Group (RTOG) 9413 trial, which used a 2 × 2 factorial design, although the initial result showed that, in combination with hormonal therapy, pelvic RT improved progression‐free survival (PFS) compared with prostate‐only RT , an updated analysis of the trial found no significant difference in PFS or OS between the two RT approaches among the patients alive after a median follow‐up of 7 years .…”
Section: Resultsmentioning
confidence: 99%
“…In the randomized phase III Radiation Therapy Oncology Group (RTOG) 9413 trial, which used a 2 × 2 factorial design, although the initial result showed that, in combination with hormonal therapy, pelvic RT improved progression‐free survival (PFS) compared with prostate‐only RT , an updated analysis of the trial found no significant difference in PFS or OS between the two RT approaches among the patients alive after a median follow‐up of 7 years . Another trial, GETUG‐01, found no significant difference in PSA‐PFS between pelvic and prostate‐only RT , but a main limitation of that study was that the upper border of the pelvic RT used was at the S1/S2 level, which is lower than the L5/S1 or L4/L5 in pelvic RT that is typically used for capturing at‐risk pelvic nodes. To further investigate the role of pelvic RT, RTOG 0924, a phase III randomized trial , will recruit 2500 men with unfavourable intermediate‐ or high‐risk PCa to receive ADT plus either prostate‐alone or pelvic RT, with OS as the primary endpoint.…”
Section: Resultsmentioning
confidence: 99%